Escravidão e resistência: a ironia como recurso estilístico nos contos machadianos. - Oliveira, Marina Rodrigues de (2011)
This dissertation aims to investigate the value of irony as a stylistic and critical resource in the representation of Machado's vision on the problem of slavery in Brazilian society. For didactic purposes, the following short stories will be studied: Virginius (1864), Mariana (1871), Encher tempo (1876), O caso da vara (1891) and Pai contra mãe (1906). This approach constitutes an attempt to elucidate the "possible" lack of criticism in Machado's work regarding to slavery, as critics have stated for a long time. Therefore, dealing with black slavery in Brazil means to understand it not as a motivating gear of a mere economic-social system that lasted for three centuries from the sixteenth to the nineteenth century but, above all, as a subject represented at the margin, ruthlessly exploited and excluded within a society undergoing modernization. Thus, in this context, the trajectory of the black in Machado‟s short stories should be seen, by the literary perspective, as a very significant aspect in addition to the historical and cultural contexts.